Detection of onset muscle fatigue based on joint analysis of surface electromyography spectrum and amplitude - Nurul Ain Mohamad Ishak, 1989-, author; Puspa Inayat Khalid, 1966-, supervisor; Nasrul Humaimi Mahmood; Fakulti Biosains dan Kejuruteraan Perubatan (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Doktor Falsafah (Kejuruteraan Bioperubatan)) - Universiti Teknologi Malaysia, 2017